Electroencephalography as a Biomarker of Prognosis in Acute Brain Injury - Rubinos, Clio; Bruzzone, Maria Jose; Viswanathan, Vyas; Figueredo, Lorena; Maciel, Carolina B.; LaRoche, Suzette (Seminars in Neurology, 2023)
Electroencephalography (EEG) is a noninvasive tool that allows the monitoring of cerebral brain function in critically ill patients, aiding with diagnosis, management, and prognostication. Specific EEG features have shown utility in the prediction of outcomes in critically ill patients with status epilepticus, acute brain injury (ischemic stroke, intracranial hemorrhage, subarachnoid hemorrhage, and traumatic brain injury), anoxic brain injury, and toxic-metabolic encephalopathy. Studies have also found an association between particular EEG patterns and long-term functional and cognitive outcomes as well as prediction of recovery of consciousness following acute brain injury. This review summarizes these findings and demonstrates the value of utilizing EEG findings in the determination of prognosis.
Keywords: electroencephalographic biomarkers; neuroprognosis; prognosis; acute brain injury